Empirical Analysis of Tax Avoidance in Main Board Property and Real Estate Companies on IDX (2022-2024) - Jidan Pramudiya; Eko Hariyanto; Edi Joko Setyadi; Dwi Winarni (Innovation Business Management and Accounting Journal, 2025)
This study aims to examine the effect of audit quality, debt policy, capital intensity, and financial performance on tax avoidance in property and real estate sector companies listed on the Indonesia Stock Exchange during the period 2022-2024. Using multiple regression analysis of 39 observations, the results showed that only financial performance has a negative and significant effect on tax avoidance. Other variables, namely audit quality, debt policy, and capital intensity, have no significant effect. This finding supports the view that companies with high profitability tend to be more compliant with fiscal obligations in order to maintain their reputation and credibility in the eyes of stakeholders. Conversely, companies with low profitability are more prone to aggressive tax planning practices. This study provides empirical evidence that profitability is an important factor in controlling the level of tax avoidance, and emphasizes the importance of more intensive supervision of companies with weak financial performance. Policy implications suggest the need for a risk-based approach in tax supervision and reformulation of the effectiveness of the role of external auditors in detecting fiscal non-compliance.